Study on relationship between bacterial diversity and quality of Huangjiu (Chinese Rice Wine) fermentation. Issue 7 (4th June 2021) - Xie, Guangfa; Zheng, Huajun; Qiu, Zheling; Lin, Zichen; Peng, Qi; Dula Bealu, Girma; Elsheery, Nabil Ibrahim; Lu, Yin; Shen, Chi; Fu, Jianwei; Yang, Huanyi; Han, Jiongping; et al.
Abstract: Huangjiu (Chinese rice wine) is brewed in an open environment, where bacteria play an important role during the fermentation process. In this study, bacterial community structure and composition changes in the fermented mash liquid of mechanized Huangjiu, well‐fermented manual Huangjiu (wines of good qualities), and poorly fermented manual Huangjiu (wines of poor qualities: spoilage, high acidity, low alcohol content) in different fermentation stages from Guyuelongshan Shaoxing Huangjiu company were analyzed via metagenomic sequencing. And bacterial metabolic difference was analyzed via gene prediction of metabolic pathway enzymes. The results showed that the bacterial diversity degree was abundant, and the number of bacterial species in every sample was approximately 200–400. Lactic acid bacteria (LAB) dominated the bacterial community of Huangjiu fermentation, and lactobacillus was predominant species in well‐fermented Huangjiu while Lactobacillus brevis had an absolute dominance in spoilage Huangjiu. Further, gene prediction revealed that transformation of malate to pyruvate and lactate anabolism was more active in mash liquid of well‐fermented manual Huangjiu, while acetate accumulation was stronger in mash liquid of poorly fermented manual Huangjiu, which explained acidity excess reason in poorly fermented Huangjiu at gene level. Abstract : The bacterial diversity degree was abundant, and the number of bacterial species in every sample was approximately 200–400. Lactic acid bacteria (LAB) dominated the bacterial community of Huangjiu fermentation, and lactobacillus was predominant species in well‐fermented Huangjiu while lactobacillus brevis had an absolute dominance in spoilage Huangjiu.